Ownership Structure and Audit Committee Influence on Earnings Persistence in Banking Firms: Evidence from 2019–2023 - Ramadhan, Muhammad Abshar Noer; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (E-Jurnal Akuntansi; Vol 35 No 1 (2025), 2025)
The Financial Services Authority (OJK) has acknowledged that several banks have lowered their profit targets for 2024 due to single-digit profit growth in the first half of the year. As a result, banking sector profits in 2024 are expected to be lower than those recorded in the previous year. This study examines the impact of ownership structure—comprising managerial ownership, institutional ownership, and ownership concentration—as well as the role of the audit committee on the earnings persistence of banking companies from 2019 to 2023. By addressing inconsistencies in previous research findings, this study aims to provide a clearer understanding of these relationships. The analysis employs multiple linear regression using the Common Effect Model (CEM) in the EViews 12 software. The findings indicate that managerial ownership has a significant negative effect on earnings persistence, while institutional ownership does not exhibit a significant influence. Conversely, ownership concentration and the audit committee positively and significantly affect earnings persistence. Moreover, the study confirms that ownership structure and the audit committee, when considered simultaneously, have a significant impact on earnings persistence.  Keywords: Ownership Structure; Audit Committee; Earnings Persistence.